Analysis of Difficulties Faced by Students in Speaking English: A Case Study at Seventh Grade of SMPN 2 Labuapi in Academic Years 2024/2025 - Sa'ud, Sakina Amanatullah Adz-Dzarif; Nawawi; Amrullah (Program Studi Pendidikan Bahasa Inggris, 2025)
The study explores the challenges faced by seventh-grade students at SMPN 2 Labuapi when speaking English. The research used a qualitative methodology, including classroom observations, questionnaires, and interviews with students and teachers. The findings revealed that students face both linguistic and non-linguistic difficulties in speaking. Linguistic problems include a lack of grammatical knowledge, poor pronunciation due to the regional Sasak accent, and a small vocabulary. Non-linguistic difficulties include difficulty with students' shyness, anxiety, and fear of making mistakes. Then, the use of mother tongue languages, low student engagement, and negative peer interactions exacerbate these issues. These encountered difficulties are influenced by three main factors, including linguistic or language, psychological, and environmental and social factors. The study suggests that addressing these difficulties requires a comprehensive strategy to create an engaging English learning environment. The findings highlight the need for a more effective approach to improve students' English language skills.